PERAN MAGNETIC RESONANCE IMGAGING DALAM DIAGNOSIS DAN PROGNOSIS CEDERA MEDULA SPINALIS AKUT - Reyhan Eddy Yunus; Taufik Budianto; Trifonia Pingkan Siregar; Thariqah Salamah; Ramdinal Aviesena Zairinal; Mohammad Triadi Wijaya (NEURONA, 2020)
Spinal cord injury is a common type of injury that can be highly fatal. Clinically, spinal cord injury can be assessed using standardized physical examination scoring from International Standards for Neurological and Functional Classification of Spinal Cord Injury Patients, which is the American Spinal Injury Association (ASIA) impairment scale or often called as AIS. The results of this scoring will then be combined with magnetic resonance imaging (MRI) examination to determine the diagnosis and prognosis. In this case, we report a 20-year-old male complaining weakness in four extremities after traffic accident while driving a motorcycle. Based on neurological examination, the patient can barely feel a touch sensation and cannot move both his arms and legs at all. Cervical X-ray examination showed dislocation fracture on C5 level. Further MRI examination showed edema and spinal cord hemorrhage around fracture area. The findings of edema and spinal cord hemorrhage on MRI examination are useful in diagnosing and predicting the outcome of patient with spinal cord injury. Keywords: AIS score, MRI, spinal cord injury